Situation Report: Romania, 31 July 1975 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. New Leaders Elected to Supreme Council on Socio-economic Development Ceausescu Calls for Upward Revision of 1976-1980 Plan Targets Assessment of Damages and Corrective Measures in Aftermath of Floods Former Turkish Premier Bulent Ecevit Visits Romania French Premier Jacques Chirac Visits Romania New Forms of Control of Local Activity Lack of Well-Qualified Experts on Agriculture